2004
DOI: 10.1158/0008-5472.can-04-1772
|View full text |Cite
|
Sign up to set email alerts
|

Human Polynucleotide Phosphorylase ( hPNPase old-35 )

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(19 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…PNPase knockdown results in impaired mitochondrial membrane potential, which can readily affect fusion and fission (Chen et al, 2005). Interestingly, over expression of PNPase could also be harmful to cells, since it can cause increased production of ROS and inflammation (Sarkar et al, 2004). Thus, both up and down regulation of PNPase could impair cell function (Hayakawa and Sekiguchi, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…PNPase knockdown results in impaired mitochondrial membrane potential, which can readily affect fusion and fission (Chen et al, 2005). Interestingly, over expression of PNPase could also be harmful to cells, since it can cause increased production of ROS and inflammation (Sarkar et al, 2004). Thus, both up and down regulation of PNPase could impair cell function (Hayakawa and Sekiguchi, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 has been shown to be associated with DNA damage– and oncogenic stress–induced senescence of mouse and human keratinocytes, melanocytes, monocytes, fibroblasts, and epithelial cells (16, 18, 57, 58). Further, IL-6 secretion appears to be directly controlled by persistent DNA-damage signaling (ATM and CHK2), independent of the p53 pathway (59).…”
Section: The Secretory Phenotype Of Senescent Cellsmentioning
confidence: 99%
“…Most senescent cells overexpress IL-8 (CXCL-8) (see Figure 2 ), along with GROα and GROÎČ (CXCL-1 and -2; the murine CXCL-1 is named KC) (58, 66, 67). CCL family members that are generally upregulated in senescent cells include MCP-2, -4, and -1 (CCL-8, -13, and -2); HCC-4 (CCL-16); eotaxin-3 (CCL-26); and macrophage inflammatory protein (MIP)-3α and -1α (CCL-20, -3).…”
Section: The Secretory Phenotype Of Senescent Cellsmentioning
confidence: 99%
“…Senescence, via adoption of a SASP, is therefore postulated to contribute to pathogenesis through the aberrant expression of genes and proteins associated with inflammation and tissue damage, including up-regulation of enzymes that induce ROS and activate NFÎșB [147]. Although the secretory phenotype of senescent hepatocytes remains unknown, studies in other cell types (such as fibroblasts) have demonstrated that senescent cells secrete a spectrum of proteins that have been previously implicated in the promotion of disease progression in NAFLD, including pro-inflammatory cytokines (e.g., IL-6, IL-8), matrix-degrading enzymes (e.g., MMPs), and other cell signalling molecules and growth factors important to liver disease (e.g., hepatocyte growth factor, platelet-derived growth factor and connective tissue growth factor).…”
Section: A Role For Hepatocyte Senescence In Disease Progressionmentioning
confidence: 99%